Perancangan Jaringan Hotspot Untuk Peningkatan Layanan Teknologi Informasi - Sucipto Sucipto; Teguh Andriyanto; Muhammad Najibulloh Muzaki; Erna Daniati; Rini Indriati; Arie Nugroho (Antivirus : Jurnal Ilmiah Teknik Informatika, 2019)
The role of network communication is vital in this era which is the industrial era 4.0. In this era, the emphasis on digital economic patterns, artificial intelligence, big data, robotics, and so on or known as the phenomenon of disruptive innovation. Technology tools that need to be developed do not directly want sophisticated automation technology. Still, network infrastructure that is available in an agency or region that wants to reach the industrial era must be considered. This research aims at designing the network is to make the topology of private networks and public networks. It is solving private networks to optimise SIMRS application access speed. It also improves the management of public networks in the form of hotspot management. The result that can be felt among the private networks is not that the SIMRS application network will not be interrupted by the public hotspot network. Besides, public network management will be more evenly distributed with hotspot management.